Implementation And Evaluation Of Teacher Performance Supervision At SMP IT Mutiara Ilmu Bangkalan - Fitria Hanaris (International Journal of Interdisciplinary Research, 2025)
The quality of education is fundamentally determined by the performance of teachers, who act as the primary agents in translating curriculum goals into meaningful learning experiences. Effective teacher performance supervision is therefore essential to ensure accountability, professional growth, and sustainable quality improvement within educational institutions. This study aims to examine the implementation and evaluation of teacher performance supervision at SMPIT Mutiara Ilmu Bangkalan, focusing on planning, execution, leadership, monitoring, and innovation in supervisory practices. Using a qualitative approach with a case study design, data were collected through in-depth interviews, systematic observations, and document analysis. Participants included school principals, supervisors, and teachers selected through purposive sampling. The findings indicate that, although supervision planning has been established, its implementation remains constrained by limited human and technical resources. Supervision activities were carried out but lacked consistent feedback and follow-up mechanisms. Leadership demonstrated collaborative efforts, yet managerial coordination requires further strengthening. Evaluation and control of supervision were conducted progressively through formative and summative assessments, emphasizing reflective practice and continuous improvement. Moreover, creative and innovative ideas such as digital supervision records, peer mentoring, and thematic evaluation workshops have been introduced to enhance efficiency and transparency. Overall, the study concludes that teacher performance supervision at SMPIT Mutiara Ilmu Bangkalan contributes positively to the professional development of teachers but requires stronger strategic planning and digital integration to achieve optimal outcomes in educational quality.